First molecular characterization of Cryptosporidium spp. infecting buffalo calves in Brazil - Aquino, Monally Conceição Costa de [UNESP]; Widmer, Giovanni; Zucatto, Anaiza Simão [UNESP]; Viol, Milena Araúz [UNESP]; Inácio, Sandra Valeria [UNESP]; Nakamura, Alex Akira [UNESP]; Coelho, Willian Marinho Dourado [UNESP]; Perri, Silvia Helena Venturoli [UNESP]; Meireles, Marcelo Vasconcelos [UNESP]; Bresciani, Katia Denise Saraiva [UNESP] (My University, 2015)
With the aim of determining the occurrence of Cryptosporidium spp., 222 fecal samples were collected from Murrah buffalo calves aged up to 6 mo. Fecal DNA was genotyped with a nested polymerase chain reaction targeting the 18S rRNA gene and sequencing of the amplified fragment. Nested 18S PCR was positive for 48.2% of the samples. Sequence analysis showed that the most frequent species in these animals was Cryptosporidium ryanae, which was present in buffalo calves as young as 5 d. The zoonotic species Cryptosporidium parvum was detected in one animal. An uncommon Cryptosporidium 18S genotype was found in buffaloes.
Keywords: Cryptosporidiosis; Cryptosporidium ryanae; Genotype; Nested-pcr; Water buffaloes